Inequalities in the Context of the COVID-19 Pandemic: Educational Experiences of the Secondary Level in Argentina - Alucin, Silvia Vanesa (2023)
The present article aims to describe and analyze the experiences of secondary school teachers around the inequality that the pandemic made visible in the use and access to different technological resources, both at the time of pedagogical continuity in 2020, and at the time of return to schooling, in 2021. To achieve this, a corpus of 19 semi-structured interviews conducted by the ENCRESPA Network (Network for the Collaborative Study of Representations on the Pandemic in Argentina) was analyzed, within the framework of the Project Identities, experiences and social discourses in conflict around the pandemic and the post-pandemic, of the Research Program of the Contemporary Argentine Society (PISAC): The social and human sciences in the COVID-19 crisis (National Agency for the Promotion of Research, Technological Development and Innovation). The data was processed with the Atlas.ti software, by identifying and coding meaningful extracts regarding the inequality of resources, stressing the divergences between public and private schools. Among the results, it is highlighted that the access, use and appropriations of certain materials conditioned educational experiences, affecting both students and teachers. This limited the scope of the educational policies designed in the context of the pandemic, so that the links between actors, the times, the possible pedagogical strategies, the learning, and the ways of teaching were unequal. Based on this, it is concluded that education in the pandemic has been virtual, sustained, and simultaneous only for a few, while for the majority it was remote, intermittent and asynchronous. The data analyzed is a valuable input to rethink educational policies, highlighting the needs that appear on the ground and the pending debts regarding inclusion. In this sense, greater dialogue is recommended between the macro (state) and micro (school) levels, to build policies more linked to institutional realities.